2015
DOI: 10.4236/msce.2015.31013
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Properties of Novel Non-Ionic Polyurethane Dispersion Based on Hydroxylated Tung Oil and Alicyclic Isocyanates

Abstract: Hydroxylated Tung oil (HTO) based nonionic polyurethane dispersion (HTO-NPUD) were synthesized using dicyclohexyl methane diisocyanate (HMDI) and HTO as main hydrophobic materials whereas polyethylene glycol-800 (PEG-800) as hydrophilic chain extender. To effectively study the effects of HTO on properties of NPUD, polypropylene glycol-400(PPG-400) based NPUD was prepared by HMDI reacting with PPG-400 and PEG-800. The structures of those novel nonionic polyurethane dispersions were characterized by FTIR and 1 H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Anionic water-borne polyurethanes are the main finishing agents for leather, while cationic water-borne polyurethanes are used as sealers and primers in order to give leather a soft, natural, and plump appearance [45]. They have been used as a softener and anti-wrinkle agent for fabrics by many companies and are very popular with consumers [46].…”
Section: Coatingsmentioning
confidence: 99%
“…Anionic water-borne polyurethanes are the main finishing agents for leather, while cationic water-borne polyurethanes are used as sealers and primers in order to give leather a soft, natural, and plump appearance [45]. They have been used as a softener and anti-wrinkle agent for fabrics by many companies and are very popular with consumers [46].…”
Section: Coatingsmentioning
confidence: 99%
“…This dispersion can be used as a potential surfactant to improve the initial performance of marking coatings. Vikash Mishra [20] and others prepared a new waterborne UV curable polyurethane dispersion using castor oil, IPDI, DMPA, and HEMA as raw materials by acetone method. The results show that these new UV PUDs have application potential in coatings.…”
Section: Introductionmentioning
confidence: 99%
“…Coatings are a kind of polymer material with complex and diverse molecular structures, and molecular chains will break during oxidation [20,21]. In the oxidation resistance process of plastics, rubber, and other polymers, it is found that the addition of antioxidants and light stabilizers can effectively slow down the aging of polymers and prolong the service life of polymers [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Prior to introducing into PUD, tung oil should be modified into polyol. In this study, the hydroxylation of tung oil (HTO) is obtained by modifying the glyceride so that the three conjugated double bonds could be remained in HTO [14,15]. The main structures of HTO are shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%